2013
DOI: 10.1074/jbc.m113.496869
|View full text |Cite
|
Sign up to set email alerts
|

The Power of Two

Abstract: Background: ␣-Amino-␤-carboxymuconate-⑀-semialdehyde decarboxylase is a key enzyme that controls quinolinic acid levels. Results: Two arginines, including one from a neighboring subunit, are required for substrate binding. Conclusion: Dimerization and two arginine residues are required for activity. Significance: This study provides the first structurally proven example of a functionally active heterodimer hybrid resulting from a simple mixing of two inactive homodimer mutants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…3d ). The moiety that gives rise to this new absorbance band is stable for minutes at room temperature and cannot be separated from the protein by membrane filtration-based methods 20 , suggesting that it is covalently bound to the protein. The formation of an enzyme–substrate adduct in the E268A mutant was investigated by mass spectrometry.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3d ). The moiety that gives rise to this new absorbance band is stable for minutes at room temperature and cannot be separated from the protein by membrane filtration-based methods 20 , suggesting that it is covalently bound to the protein. The formation of an enzyme–substrate adduct in the E268A mutant was investigated by mass spectrometry.…”
Section: Resultsmentioning
confidence: 99%
“…ACMS was generated by catalysing the insertion of molecular oxygen to 3-hydroxyanthranilic acid by purified, Fe 2+ reconstituted 3-hydroxyanthranilate 3,4-dioxygenase as described previously 16 20 . 2-HMS is generated non-enzymatically from ACMS following a previously established method 24 .…”
Section: Methodsmentioning
confidence: 99%
“…The X-ray crystal structure of this enzyme was recently solved, and biochemical work has shown a potential mechanism for regulating the activity of this enzyme. It was shown that only the homo-dimer form of ACMSD is able to catalyze the decarboxylation of the substrate, opening the door to the possibility that modulation of the quaternary structure of ACMSD may be the dominant regulatory mechanism for this enzyme [19, 20]. Another interesting feature of ACMSD is that both its substrate and its product are unstable and will undergo electrocyclizations to QUIN and picolinic acid, respectively.…”
mentioning
confidence: 99%
“…Answering this question will require detailed knowledge of the enzymatic mechanism of HAO, ACMSD, and the next enzyme in the pathway, α-aminomuconate-ε-semialdehyde dehydrogenase (AMSDH). The structure and mechanism of ACMSD are relatively well studied [19, 20], and the structure of HAO is defined [23]. However, little was known about this third enzyme, which presumably controls the partitioning between further metabolism and picolinic acid formation, until very recently, when the crystal structure was solved, and catalytic mechanism proposed [22].…”
mentioning
confidence: 99%
“…On the other hand, docking analysis revealed that carboxyl and hydroxyl groups of 2H1NA are hydrogen bonded with Arg33/Tyr272 and Tyr272 of HndA, respectively. Interestingly, the importance of the arginine residue in substrate binding via carboxylate group has been suggested in ACMSD (33,48). Similarly, the role of the active-site tyrosine residue in the binding of the hydroxyl group of lactic acid was studied in flavocytochrome b 2 or L-lactate dehydrogenase, and it was reported to play a role in converting lactic acid to pyruvic acid (49).…”
Section: Discussionmentioning
confidence: 99%